INOVASI PELAYANAN PUBLIK MELALUI MAL PELAYANAN PUBLIK KABUPATEN SIAK TAHUN 2024 - Fatimah, Siti; Nisaa, Fadhiilatun (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Based on Siak Regent Regulation Number 7 of 2024 concerning the Implementation of Public Service Malls, it was stated that in its implementation there are still various problems that hinder the achievement of optimal services. These problems include the low level of coordination between agencies that are members of the MPP, the lack of consistency in the presence of officers at certain counters, and the unequal understanding of the public regarding the functions and benefits of MPP. The purpose of the study was to determine the innovations made by the government in improving the quality of public services at the Public Service Mall and the factors that influence public service innovation through the Siak Regency Public Service Mall in 2024. This study was conducted using a qualitative approach and descriptive analysis. The types of data used are primary and secondary data. Primary data is the result of interviews with informants, while secondary data is supporting data obtained from related documents. Data collection techniques were carried out through interviews, documentation, and observation. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of the study indicate that the existence of the MPP provides convenience for the public in accessing administrative services in a fast, efficient, and centralized manner. A total of 25 agencies are involved, offering 176 types of licensing and non-licensing services. This innovation has proven to offer relative advantages, alignment with community needs, observable outcomes, and has undergone trial phases before its official launch. However, challenges remain, such as inter-agency coordination, vacancies at some service counters, and limited public participation. The main supporting factors include the availability of facilities and infrastructure, a strategic location, and strong support from the local government. Keywords: Public Service Innovation, Public Service Mall, Service Quality